2020
DOI: 10.3390/su12062229
|View full text |Cite
|
Sign up to set email alerts
|

Examining Hybrid and Single SVM Models with Different Kernels to Predict Rock Brittleness

Abstract: The aim of this study was twofold: (1) to assess the performance accuracy of support vector machine (SVM) models with different kernels to predict rock brittleness and (2) compare the inputs’ importance in different SVM models. To this end, the authors developed eight SVM models with different kernel types, i.e., the radial basis function (RBF), the linear (LIN), the sigmoid (SIG), and the polynomial (POL). Four of these models were developed using only the SVM method, while the four other models were hybridiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 69 publications
0
41
1
2
Order By: Relevance
“…Further tests and evaluation on the MI-based machine learning models revealed that the maximum possible accuracy of the best performer algorithm (SVM radial) remains bracketed around 96–97% in terms of accuracy, precision, and recall. The rbf kernel was chosen because it is most frequently used by contemporary researchers [ 30 , 74 , 75 ]. It would be logical to evaluate the other kernels before moving to the improvisation of the kernel function for improving the performance of the MI-based algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…Further tests and evaluation on the MI-based machine learning models revealed that the maximum possible accuracy of the best performer algorithm (SVM radial) remains bracketed around 96–97% in terms of accuracy, precision, and recall. The rbf kernel was chosen because it is most frequently used by contemporary researchers [ 30 , 74 , 75 ]. It would be logical to evaluate the other kernels before moving to the improvisation of the kernel function for improving the performance of the MI-based algorithm.…”
Section: Resultsmentioning
confidence: 99%
“…Such strings are used by biologically motivated operators (e.g., cross-over and mutation) to produce a new set of strings. The selection, crossover, and mutation process will continue for a fixed number of generations until certain conditions are matched [139,140]. The process of the RCGA experimental search diagram is presented in Figure 2.…”
Section: Real-coded Genetic Algorithm (Rcga)mentioning
confidence: 99%
“…In the formula, K(x i , x j ) is the kernel function, which needs to meet Mercer condition. In this paper, Gaussian RBF kernel function [46] is selected as…”
Section: Abc-svrmentioning
confidence: 99%